Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1111/j.1346-8138.2003.tb00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Diseases in Children

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 18 publications
3
30
0
Order By: Relevance
“…Its prevalence in adults is difficult to estimate and, although rare in children, may occur following sexual abuse. Pandhi et al (2003) found chancroids in both boys and girls between the ages of 10-14 group. 3 Acquired syphilis should be suspected in symptomatic or seropositive children in whom no evidence of congenital syphilis was documented.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Its prevalence in adults is difficult to estimate and, although rare in children, may occur following sexual abuse. Pandhi et al (2003) found chancroids in both boys and girls between the ages of 10-14 group. 3 Acquired syphilis should be suspected in symptomatic or seropositive children in whom no evidence of congenital syphilis was documented.…”
Section: Discussionmentioning
confidence: 99%
“…Pandhi et al (2003) found chancroids in both boys and girls between the ages of 10-14 group. 3 Acquired syphilis should be suspected in symptomatic or seropositive children in whom no evidence of congenital syphilis was documented. Almost always associated with sexual abuse, it therefore reflects the epidemiology of syphilis in adults.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations